2013
DOI: 10.2527/jas.2012-5999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding system and slaughter age on the growth and carcass characteristics of tropical-breed steers1

Abstract: This study aimed to compare the growth performances and carcass characteristics of tropical-breed steers reared in 2 contrasted feeding systems (indoor vs. pasture) and slaughtered at different ages (early vs. late). A total of 309 Creole steers (growing at an initial BW of 173 ± 3 kg and an initial age of 252 ± 4 d) were used over a continuous 12-yr study. Indoor steers were housed in a cattle shed, fed fresh-cut grass plus concentrate, and slaughtered at 14.5 or 17.1 ± 0.1 mo of age. Pasture steers were past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
2
8
0
1
Order By: Relevance
“…In trough-fed animals, which are usually diet supplemented, the greater amount of energy intake induced a linear response with more fat accretion whereas in pasture-fed animals, daily energy intake may provide enough energy to cover potential requirements, as previously suggested (Carrasco et al, 2009;data included). This finding is also consistent with decreased fat deposition and increased muscle percentages observed in grazing animals (Carrasco et al, 2009;Blanco et al, 2010;Agastin et al, 2013). This finding is also consistent with decreased fat deposition and increased muscle percentages observed in grazing animals (Carrasco et al, 2009;Blanco et al, 2010;Agastin et al, 2013).…”
Section: Effect Of Feeding Environment On Growth Performances and Carsupporting
confidence: 89%
See 1 more Smart Citation
“…In trough-fed animals, which are usually diet supplemented, the greater amount of energy intake induced a linear response with more fat accretion whereas in pasture-fed animals, daily energy intake may provide enough energy to cover potential requirements, as previously suggested (Carrasco et al, 2009;data included). This finding is also consistent with decreased fat deposition and increased muscle percentages observed in grazing animals (Carrasco et al, 2009;Blanco et al, 2010;Agastin et al, 2013). This finding is also consistent with decreased fat deposition and increased muscle percentages observed in grazing animals (Carrasco et al, 2009;Blanco et al, 2010;Agastin et al, 2013).…”
Section: Effect Of Feeding Environment On Growth Performances and Carsupporting
confidence: 89%
“…Trough-fed animals were fatter and had less muscle and bone than pasture-fed animals in proportion, in line with Agastin et al (2013;data not included). Trough-fed animals were fatter and had less muscle and bone than pasture-fed animals in proportion, in line with Agastin et al (2013;data not included).…”
Section: Effect Of Feeding Environment On Growth Performances and Carsupporting
confidence: 62%
“…Pethick et al [ 69 ] suggested that a prolonged feeding period gives the cattle time to obtain high IMF levels because time is needed for muscle to reach maturity, followed by time for the muscle to fill up with IMF. However, feed efficiency decreases as animals age due to a decrease in the rate of muscle growth [ 70 ]. Thus, animals with low genetic potential for QG are not recommended for a long fattening stage, which would result in low feed efficiency.…”
Section: Management Factorsmentioning
confidence: 99%
“…Nowadays, except for some market niches, carcasses should have a greater proportion of muscle and minimum amount of fat. Fat content should be just enough to prevent dehydration and darkening under refrigeration and to ensure meat juiciness and taste (Luchiari Filho 2000;Agastin et al 2013). Adequate carcass yield and fat thickness (FT) should be achieved taking economic aspects into consideration.…”
Section: Introductionmentioning
confidence: 99%